2014
DOI: 10.5152/tjg.2014.4081
|View full text |Cite
|
Sign up to set email alerts
|

Significance of appetite hormone ghrelin and obestatin levels in the assessment of the severity of acute pancreatitis

Abstract: Background/Aims: Due to risk of morbidity and mortality, various tests and scoring systems used in the assessment of the diagnosis and severity of acute pancreatitis disease are gaining more importance every day. Most of the current scoring systems, validated by various parameters, have a sophisticated and complex structure. Research is ongoing to establish a method to diagnose the disease and determine the severity by using different and simple parameters. In this trial, we aimed to investigate the role of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
1
6
0
2
Order By: Relevance
“…Several studies have shown that acute obestatin treatment and chronic treatment with native or modified obestatin can alter triglyceride levels, [ 4 , 27 ] suggesting that obestatin is involved in the lipid metabolism. In this study, serum obestatin levels in patients with AP were elevated at admission, but were not correlated with AP severity; these findings are consistent with those of Kanat et al [ 18 ] Unlike serum ghrelin levels, serum obestatin levels differed significantly between patients with AP caused by hypertriglyceridemia and those with AP of other etiologies. In addition, these patients had higher BISAP, Ranson, and MCTSI scores than did patients with AP of other etiologies, and the hypertriglyceridemia etiology group included significantly fewer patients with MAP than did the other 3 etiology groups.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Several studies have shown that acute obestatin treatment and chronic treatment with native or modified obestatin can alter triglyceride levels, [ 4 , 27 ] suggesting that obestatin is involved in the lipid metabolism. In this study, serum obestatin levels in patients with AP were elevated at admission, but were not correlated with AP severity; these findings are consistent with those of Kanat et al [ 18 ] Unlike serum ghrelin levels, serum obestatin levels differed significantly between patients with AP caused by hypertriglyceridemia and those with AP of other etiologies. In addition, these patients had higher BISAP, Ranson, and MCTSI scores than did patients with AP of other etiologies, and the hypertriglyceridemia etiology group included significantly fewer patients with MAP than did the other 3 etiology groups.…”
Section: Discussionsupporting
confidence: 91%
“…[ 14 , 15 ] The administration of obestatin inhibited the development of AP in a rat model, [ 16 , 17 ] but few studies have investigated the role of endogenous obestatin in human patients with AP. [ 18 ] Thus, this study was designed to assess serum ghrelin and obestatin levels in patients with AP, and to determine whether these 2 indexes have predictive value as biomarkers in AP.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, obestatin has been shown to protect against acute pancreatitis in rats, induced by either cerulein or ischaemia/reperfusion, via increasing pancreatic blood supply in parallel with reduced inflammation and digestive enzyme activity, and also to promote pancreatic repair and regeneration in these animals (Ceranowicz et al ., ; Bukowczan et al ., ). Indeed, circulating obestatin levels are increased in patients with acute pancreatitis (Kanat et al ., ), supporting a protective function in this setting.…”
Section: Metabolic Actions Of Obestatinmentioning
confidence: 52%
“…Pancreas and fatty tissue appear to be influential among the mechanisms that regulate appetite, the central nervous system, the gastrointestinal system (GIS), several anorexigenic and orexigenic peptides, and hormonal mediators released from the adrenals (1)(2)(3)(4)(5). Particular emphasis is being put on the leptin and ghrelin system in the pathophysiology of many diseases that affect appetite (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%